Видовий склад роду Pinus L. у сучасній флорі України - Marynych, I.S.; Balabushka, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
On the base of literary data and own researches was determined species composition of genus Pinus in the contemporary flora of Ukraine and widening of pines in natural and cultural stands.